Fibrinogen concentrate for bleeding in patients with congenital fibrinogen deficiency: Observational study of efficacy and safety for prophylaxis and treatment. Issue 8 (11th October 2020) - Lasky, Joseph; Teitel, Jerome; Wang, Michael; Dalton, Danielle; Schmidt, Dirk Steffen; Brainsky, Andres
Abstract: Background: Congenital fibrinogen deficiency (CFD) is a rare bleeding disorder characterized by reduced levels (afibrinogenemia, hypofibrinogenemia) or dysfunctional fibrinogen (dysfibrinogenemia), for which fibrinogen supplementation is the mainstay treatment. Objectives: To assess the efficacy and safety of human fibrinogen concentrate (FCH) in patients with CFD. Methods: This was a multicenter, noninterventional, retrospective cohort study with a 12‐month prospective follow‐up period in the United States and Canada. Individuals with CFD who received FCH for the treatment of bleeding, perioperative hemostasis, or prophylaxis were included. Data were collected retrospectively from medical records and every 3 months during the prospective period. Hemostatic efficacy was rated by the investigators as effective or ineffective using a 4‐point efficacy scale. Annualized bleeding rate (ABR) was summarized for patients who received FCH for routine prophylaxis. Results: Twenty‐two patients were enrolled. FCH treatment was rated effective in treating ≥97.0% of bleeding events, in the retrospective and prospective periods. FCH was effective for perioperative hemostasis in ≥97.5% of minor and major surgeries across both periods. In patients treated with FCH for routine prophylaxis, the median ABRs for the retrospective and prospective period were 1.4 and 1.3, respectively. One adverse event (AE), thrombosis of the right cephalic vein, was reported as related to FCH treatment and resolved with a short course of anticoagulant. No serious AEs related to FCH or deaths were reported. Conclusions: In patients with CFD, FCH is a well‐tolerated and effective treatment to achieve hemostasis during bleeding events and surgery and associated with infrequent bleeding events when used prophylactically.